Health-related quality of life in congenital heart disease surgery in children and young adults: a systematic review and meta-analysis. Issue 4 (20th April 2019) - Ladak, Laila Akbar; Hasan, Babar Sultan; Gullick, Janice; Gallagher, Robyn
Abstract : Background: As survival improves in the congenital heart disease (CHD) population, health-related quality of life (HRQOL) outcomes become increasingly important. While surgery improves survival, poor HRQOL occurs postoperatively and cardiac-related HRQOL outcomes are rarely reported. Objective: To conduct a systematic review and meta-analyses of general and cardiac-related HRQOL in CHD surgical children and young adults. Method: Medline, CINAHL and EMBASE were searched. Quantitative designs with a minimum of 80% CHD surgical patients and mean age ≤18 years compared with healthy controls were included in the review. Data were analysed in RevMan V.5.3 using a random effects model. Outcome measures: General and cardiac-related HRQOL. Results: Studies (n=20) were conducted in high-income countries and included 3808 patients plus 2951 parental reports of patients. HRQOL was worse in postoperative patients with CHD versus healthy controls in all domains with the largest difference seen for physical function (standard mean difference (SMD) of −0.56, 95% CI −0.82 to −0.30). Cardiac-related HRQOL was worse in complex compared with simple CHD with the largest SMD (−0.60, 95% CI −0.80 to −0.40) for symptoms. Heterogeneity ranged from 0% to 90%. Conclusions: CHD surgical patients have substantially worse HRQOL compared with age-matched healthy controls. Strategies should focus on improving HRQOL in this subgroup. Results may not be applicable to low/middle-income countries given the dearth of relevant research.